Lagrangian heuristic for supply perishable products in two-echelon distribution network. Issue 2 (2019) - Kande, Sona; Prins, Christian; Belgacem, Lucile; Lhermitte, Thibault
This article presents a planning problem in a distribution network incorporating two levels inventory management of perishable products, lot-sizing, multi-sourcing and transport capacity with a homogeneous fleet of vehicles. This study is carried out in collaboration with a designer of an advanced planning system (APS) software. This type of network has been encountered in recent years by several customers, such as in the distribution of dairy products or beverages and with instances that can reach large sizes. A mixed integer linear programming (MILP) is developed to solve this real planning problem. There are some instances for which the solver cannot give a good lower bound within the maximum calculation time and for other instances it takes a lot of time to solve MILP. A Lagrangian relaxation is implemented to evaluate these instances. A repair heuristic is applied to the corresponding solutions, for which the cost tends to fall during iterations.